Kinetics of Circulating Extracellular Vesicles Over the 24‐Hour Dosing Interval After Low‐Dose Aspirin Administration in Patients at Cardiovascular Risk - Liani, Rossella; Simeone, Paola Giustina; Tripaldi, Romina; D'Ardes, Damiano; Creato, Valeria; Pepe, Raffaele; Lessiani, Gianfranco; Bologna, Giuseppina; Cipollone, Francesco; Marchisio, Marco; Lanuti, Paola; Santilli, Francesca (Clinical pharmacology and therapeutics, 2023)
Extracellular vesicles (EVs) are small vesicles deriving from all cell types during cell activation, involved in transcellular communication, and regarded as predictors of vascular damage and of cardiovascular events. We tested the hypothesis that, in patients on chronic low‐dose aspirin treatment for cardiovascular prevention, aspirin may affect the release of EVs within the 24‐hour interval. We enrolled 84 patients, mostly at high or very high cardiovascular risk, on chronic low‐dose aspirin treatment. The numbers of circulating EVs (cEVs) and annexinV+ cEVs (total, platelet‐derived, endothelial‐derived, and leucocyte‐derived) were assessed immediately before, and after 10 and 24 hours of a witnessed aspirin administration. Platelet cyclooxygenase 1 (COX‐1) recovery was characterized by measuring serum thromboxane B2 (sTXB2) at the same timepoints. Nine healthy participants were also enrolled. In patients, daily aspirin administration acutely inhibited after 10 hours following aspirin administrations the release of cEVs (total and leukocyte‐derived) and annexinV+ cEVs (total, platelet‐derived, endothelial‐derived, and leukocyte‐derived), with a rapid recovery at 24 hours. The inhibition after 10 hours suggests a COX‐1–dependent mechanism. Interestingly, the slope of platelet‐derived and of annexinV+ platelet‐derived cEVs were both directly related to sTXB2 slope and COX‐1 messenger RNA, raising the hypothesis that vice versa, cEVs may affect the rate of COX‐1 recovery and the subsequent duration of aspirin effect. In healthy participants, no circadian difference was observed, except for leukocyte‐derived cEVs. Our findings suggest a previously unappreciated effect of aspirin on the kinetics of a subset of cEVs possibly contributing to the cardioprotective effects of this drug.